The Influence of Religiosity, Social Influence on Purchase Interest at Fashion Ethica Ponorogo with Attitude as a Mediating Variable - Nurrika Tiara Safitri; Fery Setiawan; Setyo Adjie (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2025)
The growth of the Muslim fashion industry in Indonesia has increased in line with public awareness of religious values ​​in clothing. This study aims to analyze the influence of religiosity and social influence on consumer purchasing interest in Ethica fashion goods in Ponorogo, with consumer attitudes as a mediating variable. Using a quantitative approach and survey method, data was collected from 140 respondents who are active consumers of Ethica goods. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results indicate that religiosity and social influence significantly affect consumer attitudes and purchasing interest. Additionally, consumer attitudes were found to play a significant mediating role in strengthening the relationship between independent variables and purchasing interest. The R-square values ​​of 67.2% for purchase intention and 59.3% for attitude indicate the model's high predictive power. These findings provide practical contributions for Muslim fashion industry practices to integrate religious values ​​and social approaches into marketing strategies, as well as enriching theoretical studies on Muslim consumer behavior through social and religious psychological approaches.